From ‘traditional’ remedies to ‘modern’ supplements: a systematic review and meta-analysis of pharmaceutical adulteration in weight-loss natural products - Phan, Dang Thuc Anh; Kongkaew, Chuenjid; Heinrich, Michael; Dao, Thi Cam Minh; Vo, Thi Ha (Frontiers in Pharmacology, 2025)
IntroductionThe World Health Organization has identified obesity as an escalating public health concern affecting millions globally, contributing to the increasing demand for anti-obesity supplements. Traditional medicinal systems, such as Ayurveda and Traditional Chinese Medicine, have historically incorporated botanicals for weight management within a holistic therapeutic framework. However, the widespread commercialization of herbal weight-loss products has resulted in misrepresentation of traditional knowledge and the frequent adulteration of these formulations with synthetic pharmaceuticals to enhance their effectiveness. This phenomenon not only raises ethical concerns regarding the exploitation of traditional medicine but also presents significant health risks to consumers.ObjectivesIn order to develop a longer-term strategy to overcome the challenges of poor quality and adulterated products making medical claims, this study aims to (1) estimate the prevalence of pharmaceutical adulteration in weight-loss natural products; and (2) examine the characteristics of such adulterations.MethodsA systematic search of PubMed, CINAHL, and Google Scholar was conducted to identify relevant studies up to July 2024. The Der Simonian-Laird random-effects model was used for data pooling. Subgroup analyses and a meta-regression model were utilized to explore potential sources of heterogeneity. The quality of the included studies was assessed using the Toxicological Data Reliability Assessment Tool (ToxRTool).ResultsA total of 26 studies qualified for the systematic review, while 22 studies were included in the meta-analysis. The estimated prevalence of synthetic adulteration exhibited significant variability, ranging from 0% to 100%, with an overall pooled median estimate of 37.5% (Interquartile range (IQR) 25.9%–49.6%). The prevalence of sibutramine adulteration was found to have a median rate of 21.8% (IQR 11.9%–33.5%). The subgroup analysis revealed a high prevalence of synthetic adulteration in Europe, particularly during the years 2012–2014, with a notable occurrence in samples collected from local markets.ConclusionThis systematic review and meta-analysis highlights the high prevalence of intentional adulteration in weight-loss natural products, with sibutramine as the most common adulterant. To protect public health and market integrity, a global framework is needed, emphasizing harmonized regulations, international collaboration, and public awareness. Future research should assess long-term health effects to ensure sustainable and safe healthcare solutions worldwide.